Effect Of Cost Of Goods Sold On Clove Commodity Farmers’ Income With Momosad As A Moderating Variable - Sabrina Mutiarahma Mamonto; Tri Handayani Amaliah; Ronald S. Badu (Economics and Digital Business Review, 2026)
This research aims to analyze the effect of cost of goods sold {COGS) on clove farmers’ income and to examine the role of momosad as a moderating variable in the relationship between COGS and clove farmers’ income in Buyandi Village, Modayag Subdistrict. This research employs a quantitative approach with a survey method through questionnaire distribution. The population consisted of all clove farmers in Buyandi Village, Modayag Subdistrict. Using a nonprobability sampling technique, a sample of 50 clove farmers who met the criteria was selected. Data analysis techniques employed multiple linear regression with a moderated regression approach, assisted by SPSS version 20. The results show that the cost of goods sold has a positive and significant effect on farmers’ income. Furthermore, momosad, as a form of traditional mutual cooperation, directly demonstrates a positive and significant effect on farmers’ income. However, the moderation test results indicate that momosad provides a negative and significant influence on the relationship between COGS and farmers’ income. This suggests that although momosad directly improves production process efficiency, as a moderating variable, momosad weakens the relationship between COGS and farmers’ income. These findings indicate that social factors cannot always strengthen economic relationships based solely on cost calculations.